The effect of δ-hydride on the micromechanical deformation of a Zr alloy studied by in situ high angular resolution electron backscatter diffraction. (December 2019) - Wang, Siyang; Kalácska, Szilvia; Maeder, Xavier; Michler, Johann; Giuliani, Finn; Britton, T. Ben
Abstract: Zircaloy-4 (Zr-1.5%Sn-0.2%Fe-0.1%Cr wt%) is used as nuclear fuel cladding materials and hydride embrittlement is a major failure mechanism. To explore the effect of δ-hydride on plastic deformation and performance of Zircaloy-4, in situ high angular resolution electron backscatter diffraction (HR-EBSD) was used to quantify stress and geometrically necessary dislocation (GND) density during bending tests of hydride-free and hydride-containing single crystal Zircaloy-4 microcantilevers. Results suggest that while the stress applied was accommodated by plastic slip in the hydride-free cantilever, the hydride-containing cantilever showed precipitation-induced GND pile-up at hydride-matrix interface pre-deformation, and considerable locally-increasing GND density under tensile stress upon plastic deformation. Graphical abstract: Unlabelled Image